Citizen security as a fundamental element for human development: analysis crimes in Chile using a spatiotemporal logistic model - Cadena-Urzúa, Pablo; Iftimi, Adina; Montes-Suay, Francisco (Iberoamerican Journal of Development Studies, 2023)
Citizen security is an essential condition for the realization of people; in contribution to this, the objective of the article is to provide relevant information on the behavior of crime, analyzing the crimes of greater social connotation that occurred in the communes of the Metropolitan Region of Chile. The chosen method is a logistic model, which includes socioeconomic and demographic covariates of each commune, as well as spatial and temporal effects. In the case of the former, it highlights the importance of the population, infant mortality, permanent personal income, and poverty as factors that significantly increase the probability of committing crimes, especially robbery in all its forms. In this same order of ideas, school attendance and green areas reduce the occurrence of crimes. Crimes that stand out for their extreme violence, such as homicide and rape, occur with greater probability on Saturday and Sunday, besides on Friday, for the crimes of lesions and robbery with violence. This type of analysis is important because it allows identifying criminal patterns that crime can adopt, all aimed at focused and evidence-based crime prevention, to contain crime and, thus, favor human development, which that allows the individual and the community to realize their legitimate aspirations.